Specific structural changes in Parkinson’s disease-related olfactory dysfunction compared to others forms of olfactory dysfunction - Brosse, Sarah; Tremblay, Cécilia; Mérida, Inés; Frasnelli, Johannes (Frontiers in Neural Circuits, 2024)
Context: Olfactory dysfunction (OD) is a common early symptom of Parkinson's disease (PD). However, OD is not specific to PD, as approximatively 20% of the general population exhibit different forms of OD. To use olfactory measures for early Parkinson screening, it is crucial to distinguish PD-related OD from Non-Parkinsonian OD (NPOD). Objectives and hypothesis: This study aimed to compare the structural changes associated with PD-related OD (n=15) with NPOD (n=15), focusing on grey matter volumes and white matter fiber integrity in chemosensory regions. We hypothesized that PD-related OD presents specific structural alterations in these regions.Methods: Participants underwent a 3T MRI scan, which included anatomical T1 and diffusion-weighted imaging. Grey and white matter integrity were assessed using both whole-brain analyses (voxel-based morphometry -VBM and tract-based spatial statistics -TBSS, respectively) and localized approaches, including regions of interest and tractography. Results: PD patients exhibited significantly higher grey matter volume in the left insula using restricted regions-of-interest analyses, while no other significant grey or white matter differences were found between groups. Conclusion: Structural imaging of the grey matter, particularly the insula, but not of white matter, differentiates PD-related OD from NPOD.